Implikasi Kepemimpinan Situasional pada Efektivitas Prestasi Kerja TU di Sekolah Menengah Pertama Negeri 23 Semarang - Burhanuddin Chusnul Chuluq; Agus Khunaifi; Fanzal Pamungkas (Jawda: Journal of Islamic Education Management, 2021)
The leader is the person who is authorized to lead the activities in a group, the leadership role of the headmaster means a lot to the school, the success of the school is very closely related to the style and approach of the headmaster's leadership, how the headmaster manages his subordinates in order to produce the order as expected. This research is a field research with qualitative approach. The subjects of the study were the principal and administrative staff. Data obtained by interviews, observations and documentation.The results of this study concluded that there are implications of situational leadership of the principal on the effectiveness of administrative performance seen from the type of situational leadership, namely the first instruction process of the principal to the administrative admin coordinator, the second consultation process between the administration and the principal, resulting in a harmonious relationship and also intertwined two-way communication, the third process of participation when the principal is involved in the work that coincides with the administrative staff and the fourth process of delegation of the principal on administrative performance does not provide training directly to support the performance of the administration.